2012
DOI: 10.1111/j.1747-4949.2012.00809.x
|View full text |Cite
|
Sign up to set email alerts
|

Educational Campaign on Stroke in an Urban Population in Northern Germany: Influence on Public Stroke Awareness and Knowledge

Abstract: Our data indicate that stroke knowledge and awareness, which could provide earlier presentation to the emergency unit for timely treatment onset, are still low in urban Northern Germany but may decisively be increased by educational campaigns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
33
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 22 publications
(41 reference statements)
5
33
0
1
Order By: Relevance
“…The knowledge of stroke warning signs was low, although it significantly increased during the campaign ( P < 0.001) as paresis/weakness (46%) and speech problems (31%) were most frequently named. The majority of respondents indicated that the first action after suffering from stroke should be calling emergency care (74% before vs. 84% after campaign, P < 0.001) 17. In a recent review on public education campaigns by Rasura et al, 22 intervention studies and 5 web-based campaigns were included.…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge of stroke warning signs was low, although it significantly increased during the campaign ( P < 0.001) as paresis/weakness (46%) and speech problems (31%) were most frequently named. The majority of respondents indicated that the first action after suffering from stroke should be calling emergency care (74% before vs. 84% after campaign, P < 0.001) 17. In a recent review on public education campaigns by Rasura et al, 22 intervention studies and 5 web-based campaigns were included.…”
Section: Discussionmentioning
confidence: 99%
“…Educational campaigns have shown to be a cost-effective method for raising awareness of stroke [6,[15][16][17] not only in our population but also in several other countries. This emphasizes the efficiency of educational interventions depending on what population is being targeted.…”
Section: Discussionmentioning
confidence: 99%
“…Educational campaigns about stroke have proved effective among urban populations, students, and children. [2][3][4][5][6][7] However, the effectiveness of stroke educational campaigns in rural areas and for elderly persons remains unknown. We conducted stroke educational campaign at supermarkets because grocery shopping is a necessity at any age, and the average shopper goes to supermarkets twice weekly.…”
mentioning
confidence: 99%